The regulation of interdependent markets - Raffaele Fiocco; Carlo Scarpa (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
We examine the issue of whether two monopolists which produce substitutable goods should be regulated by one (centralization) or two (decentralization) regulatory authorities, when the regulator(s) can be partially captured by industry. Under full information, two decentralized agencies - each regulating a single market - charge lower prices than a unique regulator, making consumers better off. However, this leads to excessive costs for the taxpayers who subsidize the firms, so that centralized regulation is preferable. Under asymmetric information about the firms' costs, lobbying induces a unique regulator to be more concerned with the industry's interests, and this decreases social welfare. When the substitutability between the goods is high enough, the firms' lobbying activity may be so strong that decentralizing the regulatory structure may be social welfare enhancing.
Keywords: D82; L51; 330; regulation; lobbying; asymmetric information; energy markets; Regulierung; Zentralstaat; Dezentralisierung; Energiemarkt; Produktsubstitution; Interessenpolitik; Asymmetrische Information; Wohlfahrtseffekt; Theorie